Duration of third stage labour and postpartum blood loss: a secondary analysis of the WHO CHAMPION trial data - Sumangala B. Chikkamath; Geetanjali M. Katageri; Ashalata A. Mallapur; Sunil S. Vernekar; Manjunath S. Somannavar; Gilda Piaggio; Guillermo Carroli; José Ferreira de Carvalho; Fernando Althabe; G. Justus Hofmeyr; Mariana Widmer; Ahmet Metin Gulmezoglu; et al. (BMC, 2021)
Plain Language Summary The duration of the third stage of labour (TSL) seems to be an important risk factor for greater postpartum blood loss, as literature shows that a longer TSL can be associated with more blood loss. Active management of third stage of labour (AMTSL), included in the WHO guidelines for prevention of postpartum haemorrhage (PPH), is effective in reducing both the amount of postpartum blood loss and the duration of the third stage. To better describe the association between duration of TSL and postpartum blood loss in women receiving AMTSL, we conducted this secondary analysis of WHO CHAMPION trial data. To assess the association between the duration of third stage of labour and postpartum blood loss, a subcohort of the CHAMPION modified ITT population was selected by excluding women with missing blood loss or missing TSL duration or TSL duration more than 60 min and women with interventions. Thus, the subcohort consisted of 10,040 women. In women with vaginal birth and not receiving interventions for treating atonic PPH or other sources of bleeding, and with TSL duration up to 60 min, there was a positive association between duration of the TSL and postpartum blood loss. The blood loss rose steeply with duration in women with TSL of 10 min or less, while in women with longer TSL duration the slope was less steep. There was no evidence of a difference between oxytocin and HS carbetocin in the pattern of association of duration of the TSL and blood loss.